Clássicos brasileiros sobre literatura infantil (1943-1986) - Mortatti, Maria do Rosario Longo (Editora Oficina Universitária, 2020)
"[...] this book already in the presentation shows the research effort by Professor Maria do Rosário Longo Mortatti, a by the organizers of the volume, which indicates from the presentation the genesis of this project, that is, its restlessness born still as a teacher of basic education and the awareness of the need to take part in the training of readers. It is restlessness unfolded in Masters, Doctorate, others published books and consolidation of a research group, whose results have been socialized over the years. The result of a work that is thought from a question research, planned to meet the referrals and whose functions distributed to different voices are linked organically, it is quite different from a volume of articles in around a theme. And this volume adds the fact that part of the authors of chapters to be references in the performance as researchers and professors in the area, representing, as Professor Mortatti, dissonant voices in literary studies, in the sense of occupying themselves with reflections on the formation from the reader. In other words, it is not about the gathering of texts about children's literature, but of a clearly defined project by the organizer, which results in a cohesive and aggregating whole of unpublished and much needed reflections in the field."